Influence of extracellular polymeric substances on the aggregation kinetics of TiO2 nanoparticles. (1st November 2016) - Lin, Di; Drew Story, S.; Walker, Sharon L.; Huang, Qiaoyun; Cai, Peng
Abstract: The early stage of aggregation of titanium oxide (TiO2 ) nanoparticles was investigated in the presence of extracellular polymeric substance (EPS) constituents and common monovalent and divalent electrolytes through time-resolved dynamic light scattering (DLS). The hydrodynamic diameter was measured and the subsequent aggregation kinetics and attachment efficiencies were calculated across a range of 1–500 mM NaCl and 0.05–40 mM CaCl2 solutions. TiO2 particles were significantly aggregated in the tested range of monovalent and divalent electrolyte concentrations. The aggregation behavior of TiO2 particles in electrolyte solutions was in excellent agreement with the predictions based on Derjaguin-Landau-Verwey-Overbeek (DLVO) theory. Divalent electrolytes were more efficient in destabilizing TiO2 particles, as indicated by the considerably lower critical coagulation concentrations (CCC) (1.3 mM CaCl2 vs 11 mM NaCl). The addition of EPS to the NaCl and low concentration CaCl2 (0.05–10 mM) solutions resulted in a dramatic decrease in the aggregation rate and an increase in the CCC values. For solutions of 11 mM NaCl (the CCC values of TiO2 in the absence of EPS) and above, the resulting attachment efficiency was less than one, suggesting that the adsorbed EPS on the TiO2 nanoparticles led to steric repulsion, which effectively stabilized the nanoparticle suspension. At high CaCl2 concentrations (10–40 mM), however, the presence of EPS increased the aggregation rate. This is attributed to the aggregation of the dissolved extracellular polymeric macromolecules via intermolecular bridging, which in turn linked the TiO2 nanoparticles and aggregates together, resulting in enhanced aggregate growth. These results have important implications for assessing the fate and transport of TiO2 nanomaterials released in aquatic environments. Graphical abstract: Highlights: TiO2 particles were significantly aggregated in the tested electrolyte solutions. Ca 2+ ions were more efficient in destabilizing TiO2 NP than Na + ions. The aggregation of TiO2 NP in solutions was agreement with DLVO theory. In NaCl and low CaCl2, EPS stabilized the NP suspension due to steric repulsion. At high CaCl2, EPS increased aggregation rate of NPs by intermolecular bridging.